Employee selection and work engagement: do recruitment and selection practices influence work engagement? - Gill, David S. (Kansas State University, 2007)
Work engagement has received increased attention by both practitioners and academicians. Researchers and practitioners have focused on the antecedents of employee engagement and the positive outcomes of an employee being engaged. This study served to expand the literature on antecedents and outcomes of work engagement to include human resources practices, such as Realistic Job Previews (RJP) and selection tests, as antecedents. A sample of 161 Information Technology help desk support representatives, who were grouped by receiving or not receiving an RJP and a selection test, were assessed on the Utrecht Work Engagement Scale (Schaufeli, Salanova, Gonzalez-Roma, and Bakker, 2002). Significant differences were found for individuals who recalled receiving an RJP on work engagement. Significant differences were not found for the selection test group on work engagement. Additional analyses were conducted to determine the predictability of engagement on individual (e.g., personal health and job satisfaction) and organizational outcomes (e.g., turnover intentions and performance). Overall, results suggest that human resources practices should be included in the work engagement model. Additional research directions and organizational implications were discussed.
Keywords: Work Engagement; Employee Selection; Personal Health; Psychology, Industrial (0624)